Direito à biodiversidade e à alimentação: uma comparação das políticas de sementes do Brasil e da Argentina - Souza, Rafaela Oliveira de (2021)
The present work aims to answer the following question: have the seed policies of Brazil and Argentina contributed to the guarantee or not of the Rights to biodiversity and adequate food? The research addresses the relationship between commodification and monopolistic appropriation of seeds and the construction of seed systems in Brazil and Argentina and is carried out within the framework of the research project approved by CNPq entitled "Right to Biodiversity, Food and the Green Revolution in South America. An analysis of risks, damages and responsibilities in the seed policies of Brazil, Argentina and Bolivia". In this work we characterize and compare the legislation and public policies on seeds in both countries, demonstrating to what extent they contribute to the transformation of seeds into agricultural inputs and compromise the right to biodiversity and food. Also, based on the tension between the corporate food regime and food sovereignty movements, we verify the actions and experiences of the central subjects in the seed systems through semi-structured interviews. In the first section we present the concepts of neoliberalism and corporate diet and the process of transformation of seeds from common goods into agricultural inputs, as well as characterizing the systems of intellectual property rights over plants and formal and local seed systems. In the second section we present the methodological path taken and the socio-political context of implementing seed policies in Brazil and Argentina, and we characterize seed and crop laws, public policies and draft laws related to seeds in both countries, addressing the formal aspects and the perspective of subjects in seed systems. In the third section we present the voices of the subjects in the seed systems, addressing their experiences in the formal, local and intermediate seed systems, and we bring the main aspects of the Brazilian and Argentine seed systems and the consequences for agrobiodiversity, food sovereignty and rural populations, and finally, we present the actions, projects and experiences of promoting food sovereignty and Creole seeds, which form a network of resistance to the corporate food regime and neoliberal rationality. In this way, we understand how seed legislation in comparative countries is effective and what the consequences are for agrobiodiversity, food sovereignty, and the people of local seed systems.